Evaluation of a Solar-Recharged Micro-GPS Datalogger for Northern Bobwhite in the Rolling Plains of Texas - Byron R. Buckley; Rowdy A. White; C. Brad Dabbert (National Quail Symposium Proceedings, 2022)
The use of Global Positioning Systems (GPS) transmitters on northern bobwhite (Colinus virginianus; hereafter, bobwhite) could increase our understanding of fine-scale movements and habitat use for a declining game bird species. We evaluated solar-recharged micro-GPS dataloggers to determine the effectiveness of the units on free-ranging bobwhite and we conducted a controlled experiment to determine the accuracy of the dataloggers under a variety of canopy cover. We deployed the micro-GPS dataloggers on 25 bobwhites between August 2016 and April 2017 across 4 different ranches in the Rolling Plains of West Texas, USA. Accuracy (± standard error) for the 8 dataloggers across 3 trials for the stationary tests was 25.4 ± 3.8 m. Daily movement of bobwhite averaged 0.96 ± 0.09 km and morning movements averaged 0.49 ± 0.07 km. Average 95% and 50% minimum convex polygons for bobwhite area utilization were 15.2 ha and 3.6 ha, respectively. Our data indicate that solar-recharged micro-GPS dataloggers can be used to monitor bobwhites’ short-term fine-scale movements in West Texas.
Keywords: Colinus virginanus; daily movement; dataloggers; MCP; micro-GPS; northern bobwhite